1999
DOI: 10.1016/s0014-5793(99)00257-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable aminopeptidase from Pyrococcus horikoshii

Abstract: From the genome sequence data of the thermophilic archaeon Pyrococcus horikoshii, an open reading frame was found which encodes a protein (332 amino acids) homologous with an endoglucanase from Clostridium thermocellum (42% identity), deblocking aminopeptidase from Pyrococcus furiosus (42% identity) and an aminopeptidase from Aeromonas proteolytica (18% identity). This gene was cloned and expressed in Escherichia coli, and the characteristics of the expressed protein were examined. Although endoglucanase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 14 publications
3
40
0
Order By: Relevance
“…4). Its aminopeptidase activity stops at the residue before the first proline in the peptide, which was also observed for the related deblocking aminopeptidase homolog in archaea (1). This may be due to the unique imide bond in proline, which restricts the overall N-terminal conformation of the oligopeptides and disrupts the contacts between residues and active sites of the enzyme.…”
Section: Fig 2 Genomic Region In Ementioning
confidence: 62%
See 1 more Smart Citation
“…4). Its aminopeptidase activity stops at the residue before the first proline in the peptide, which was also observed for the related deblocking aminopeptidase homolog in archaea (1). This may be due to the unique imide bond in proline, which restricts the overall N-terminal conformation of the oligopeptides and disrupts the contacts between residues and active sites of the enzyme.…”
Section: Fig 2 Genomic Region In Ementioning
confidence: 62%
“…YpdE in E. coli shows moderate similarity (ϳ24% identity) to the previously reported metal ion-dependent deblocking aminopeptidase (PH0519) in the archaeon Pyrococcus horikoshii (1,17) and to an aminopeptidase in Haloarcula marismortui (ϳ21% identity in an ϳ150-aa region) (8). It is known that PH0519 shows broad aminopeptidase activity on nonblocked peptides and blocked peptides by acyl group (1).…”
Section: Fig 2 Genomic Region In Ementioning
confidence: 87%
“…Pyrococcus horikoshii OT3 is one of those organisms with the optimum growth temperature above 95°C (4). Based on its complete published genome sequence (8,9), we have expressed some of the enzymes from this organism and characterized them, most of which have proven to be highly thermostable (1,7). It is quite likely, therefore, that other useful enzymes that are active and stable at extremely high temperatures remain to be found.…”
mentioning
confidence: 99%
“…A new aminopeptidase from P. horikoshii has been identi®ed recently by Ando and coworkers (gene PH0519;Ando et al, 1999). They have shown that this enzyme has an aminopeptidase activity and cleaves the N-terminal amino acid from a variety of peptide substrates and that it also has a putative acylamino-acid-releasing (deblocking) activity for acyl (blocked) peptides.…”
Section: Introductionmentioning
confidence: 99%